AiroLAB: a framework toward effective virtualisation of multi-hop wireless networks. (8th April 2011) - Doriguzzi Corin, Roberto; Riggio, Roberto; Miorandi, Daniele; Salvadori, Elio
In this work, we introduce AiroLAB, a novel network virtualisation framework specifically tailored to multi-hop wireless networks. AiroLAB departs from conventional network virtualisation approaches by focusing on embedded, resource-constrained devices and by aiming at providing Wireless Internet Service Providers with an effective virtualisation mechanism where network resources are shared between production traffic and a variable number of experimental slices allowing novel solutions and services to be tested in a controlled yet realistic environment. In the paper, the design choices at the hearth of AiroLAB are presented, together with an early-stage prototype implementation and experimental results obtained in a small-scale wireless network testbed.